Prediction of Viscosity for Plasticizers using a QSPR model - A. Radhi, Wisam (Al-Qadisiyah Journal of Pure Science, 2018)
In this work, a linear quantitative structure–property relationship (QSPR) model is presented for the prediction of Viscosity[η] for Plasticizers. Structural parameters were derived from the structures of minimum energy obtained by molecular mechanics(MM+) and the semi- empirical molecular orbital (AM1) calculations. QSPR model includes some molecular properties, regression quality indicates that these descriptors provide valuable information and have significant role in the assessment of the Viscosity of Plasticizers. This model provides good results, when the model depends on eight parameters [T.E, V.W.V, Mass, H.E, LUMO,V, ΔE and HOMO], with correlation coefficient R2 = 0.905 for 21 Plasticizers.